Organic structure determination using 2-D NMR spectroscopy : a problem-based approach - Simpson, Jeffrey H. (Academic Press, 2012)
This book contains 60 quality 2D NMR data sets following an introductory section describing the methodology employed. Many other books describe the methods used, but none offer a large number of problems. Instructors at universities and colleges at the present time are forced to cobble together problems from a wide range of sources. The fragmentary approach to assembling course materials has a negative impact on course continuity and thus adversely impacts student retention. This book will stand as a single source to which instructors and students can go to obtain a comprehensive compendium of NMR problems of varying difficulty. . Presents strategies for assigning resonances to known structures and for deducing structures of unknown organic molecules based on their NMR spectra . Contains 20 known and 20 unknown structure determination problems . Features a supporting website from which instructors can download the structures of the unknowns in selected chapters, digital versions of all figures, and raw data sets for processing.